The effect of interventions distributing home fortification products on infant and young child feeding (IYCF) practices: A systematic narrative review - Lindsey M. Locks; Katharine B. Newell; Annette Imohe; Grainne M. Moloney; Linda Shaker‐Berbari; Naveen Paudyal; Maria Elena D. Jefferds (Wiley, 2023)
Abstract Interventions distributing micronutrient powders (MNPs) and small‐quantity lipid‐based nutrient supplements (SQ‐LNS), or home fortification products (HFPs), have the potential to improve infant and young child feeding (IYCF) practices and children's nutrition. We systematically searched for studies on the effect of interventions distributing HFP on IYCF practices. We identified 12 (8 MNP, 4 SQ‐LNS) studies: seven programmes with IYCF behaviour change communications (BCC) and MNP (IYCF‐MNP) and one provided MNP without IYCF BCC (MNP only). Three SQ‐LNS studies came from randomised trials without an IYCF component (SQ‐LNS only) and one from a programme with both IYCF BCC and SfQ‐LNS (IYCF‐SQ‐LNS). Five IYCF‐MNP programmes reported positive associations with some IYCF practices-four with minimum dietary diversity, two with minimum meal frequency, four with minimum acceptable diet, and three with the initiation of complementary foods at 6 months. Two reported no association between MNP and IYCF indicators, and one reported a decline in IYCF practices during the intervention, although it also reported significant changes to the IYCF programme during the evaluation period. Two studies from interventions that distributed SQ‐LNS (one from a related set of randomised controlled trials and the sole IYCF‐SQ‐LNS programme) reported a positive association with IYCF practices; one trial reported no change in breast milk intake with the provision of SQ‐LNS and one found no association with IYCF practices. SQ‐LNS and MNP can address nutrient gaps for young children in low‐resource settings; our findings indicate that programmes that combine HFP with IYCF interventions may also contribute to improved IYCF practices in some settings.